Factors That Affect Body Mass Index of Adults - Asil, Esma; Surucuoglu, Metin Saip; Cakiroglu, Funda Pinar; Ucar, Asli; Ozcelik, Ayse Ozfer; Yilmaz, Mustafa Volkan; Akan, Lale Sariye (Pakistan Journal of Nutrition, 2014)
The aim of the study is to determine the factors that contribute to the body mass index (BMI) of adults and evaluate the eating habits of the individuals. The study was conducted on 498 adults whose ages were ranging from 20 to 85 (39.1±14.9 year). The data were collected using a questionnaire form that consisted of questions concerning general characteristics of individuals, frequency of food consumption and eating habits. Food types in the food consumption frequency were grouped together according to Nutrition Guide for Turkey. Body weights and heights of the individuals were measured. BMI of the 55% of the individuals participated in the study is 25 or higher than 25. The average BMI of the individuals differs according to age, educational, marital, smoking status, parity and sleep duration (p<0.05). According to standardized regression coefficient; factors affecting BMI in the order of importance are: age (p<0.001), educational (p<0.001), marital (p<0.001), smoking status (p<0.05) and sleep duration (p>0.05). A statistically significant correlation was found between BMI of participants and their habit of eating at night, appetite and use of sweeteners (p<0.05). Individuals with BMI<25 were determined to have a lower consumption frequency of milk and dairy products and fruits-vegetables monthly (p<0.05). In this study; age, educational, marital, smoking status and sleep duration were found to affect body mass index. Analysis of genetic and environmental factors affecting obesity is required to reveal the factors affecting body mass index of individuals more clearly.